A DSPL Design Framework for SASs: A Smart Building Example - Achtaich, A.; Souissi, N.; Mazo, R.; Roudies, O.; Salinesi, C. (EAI Endorsed Transactions on Smart Cities, 2018)
The Internet of Things is a land of opportunity for believers and supporters of Smart Cities. Experience already shows that smartphones, smart appliances, wearables, sensors and actuators can be brought together to deliver advanced services like smart markets, smart parking, smart buildings or smart energy. But in order to do so in a complex, dynamic, rapidly changing and resource constrained environment, adapting fleets of devices to align with context fluctuations becomes a necessity. This paper describes the framework established to tackle the problem. It represents the dimensions for building Self-adaptive fleets for IoT applications, based on the foundations of the DSPL paradigm and the RE principles. The paper also allocates a model for each dimension of the framework, and through a preliminary proof of concept Smart Building example, confirms the usability of the proposal.